Case Report: Exome Sequencing Identified a Novel Compound Heterozygous Variation in PLOD2 Causing Bruck Syndrome Type 2 - Zhang, Jing; Hu, Huaying; Mu, Weihong; Yu, Mei; Chen, Wenqi; Mi, Dongqing; Yang, Kai; Guo, Qing (Frontiers in Genetics, 2021)
Bruck Sydrome (BRKS) is a rare type of recessive Osteogenesis imperfecta (OI) and consists of two subtypes, BRKS1 and BRKS2, which are caused by variations in FKBP10 and PLOD2 genes, respectively. In this study, a family experiencing multiple miscarriages and recurrent fetal skeletal dysplasia was recruited and underwent a multiplatform laboratory investigation. Prenatal genetic testing with whole-exome sequencing (WES) identified a compound heterozygous variation in PLOD2 gene with two variants, namely c.2038C>T (p.R680*) and c.191_201+3 delATACTGTGAAGGTA (p.Y64Cfs*12). The amino acids affected by the two variants maintained conserved across species. And the result of immunohistochemistry (IHC) indicated that the expression of PLOD2 protein in the proband's osteochondral tissue was significantly decreased. These findings in our study expanded the variation spectrum of PLOD2 gene, provided solid evidence for the counseling on future pregnancies of this family, strongly supported the application of WES in prenatal diagnosis, and might give insight into the understanding of PLOD2 function.